PERANCANGAN KEMASAN PRODUK UMKM SONOKANA BAKERY DI KABUPATEN BANDUNG - Rahmi Nurul Ihsani, Tengku; Eridani Naufalina, Fariha; Krisna Aditya, Dimas (eProceedings of Art & Design, 2024)
MSMEs (Micro, Small and Medium Enterprises) have a significant role in the country's economic growth. Based on data from the Ministry of Cooperatives and MSMEs, the contribution of MSMEs to the Indonesian economy includes the ability to absorb 97% of the total existing workforce and can collect up to 60.4% of total investment. Sonokana Bakery is an MSME that sells various types of bread and donuts inspired by Japanese butter cookies. The problems faced by Sonokana Bakery are the lack of recognition of the product by pupils and students, the lack of visual identity in the packaging design for Sonokana Bakery products, and the lack of attractiveness of Sonokana Bakery product packaging compared to similar projects. This research uses data collection methods through a qualitative approach in the form of observation, interviews, documentation and literature study, as well as visual analysis methods, SWOT matrix analysis and matrix analysis, with the aim of increasing the selling power of Sonokana Bakery products and targets through more attractive packaging designs, has a visual identity and shows complete information. With good packaging design, it is hoped that consumers will believe in the quality of Sonokana Bakery products and increase the brand quality and selling value of Sonokana Bakery products so that they can compete with other competitors and get a wider target market. Keywords: packaging design, MSMEs, Sonokana Bakery